A Composite Hydrogel Based on Pectin/Cellulose via Chemical Cross-Linking for Hemorrhage - Chen, Wancheng; Yuan, Sijie; Shen, Jie; Chen, Yongsheng; Xiao, Yang (Frontiers in Bioengineering and Biotechnology, 2021)
Hydrogel-based material has been demonstrated promising potential for hemostasis. Herein, we prepared a composite hydrogel (CH-P 40%) by combining pectin and cellulose in ionic liquid. The superficial morphology of the CH-P 40% was explored by SEM; the internal chemical bonds, crystal form and thermal stability were determined via FTIR, XRD and thermogravimetric analysis, respectively. The biocompatibilities of CH-P 40% hydrogel were evaluated by MTT, flow cytometry, and by histological observation of H＆E staining. Furthermore, the hemostatic effect was evaluated via blood clotting index and mouse liver hemostatic model. Shown as the results, the CH-P 40% hydrogel performed a dense network structure and remained the chemical bonds including OH, CH, C = O, -CH2, CO, C1-H and β-glycosidic. Simultaneously, the hydrogel reserved Cellulose I and II crystal structure and favorable thermal stability. Moreover, the CH-P 40% treated cell proliferation rates both increased (P > 0.05) and there were no pathological lesions in mouse organs, which suggesting favorable biocompatibility. The results showed the lower amount of bleeding in the hydrogel-treated liver wound within 3 minutes. Overall, the pectin-cellulose hydrogel is stable, and possesses favorable biocompatibility and hemostatic ability, further highlighting the composite hydrogel has the potential capability to be rapid hemostasis biomedical material.